CONCEPTUAL APPROACHES TO CLASSIFICATION OF NATIONAL ACCOUNTING SYSTEMS - Putihin Y.E.; Akimova Y.N.; Ostrovskaya N.V.; Manvelova I.A.; Negashev E.V. (Scientific Journal of Pedagogy and Economics, 2020)
International Accounting Practice Accounting is multifaceted and heterogeneous. First distinguish between international standards and national standards. National accounting standards for each country is being developed independently. The leading countries in the field of national accounting standards are the United Kingdom and the United States, which is determined by the role of these countries in international financial markets. In different countries, national accounting standards are called differently; in addition, various bodies are involved in their development: in some these are state bodies, in other countries professional organizations. International accounting standards are implemented and developed at 2 levels: international, global and regional. In the regional aspect, the main role belongs to the EU Accounting Commission, which regulates these matters in the EU countries. World standards are developed by several organizations: International Federation of Accountants, Committee on International Accounting Standards, Intergovernmental Group of Experts on International Standards Reporting and Accounting Center for Transnational United Nations Corporation, Economic development and cooperation. There is a great variety of accounting systems around the world. The differences between them are explained mainly by the different business environments in which they operate. Among many classifications, which are based on various principles, two main classifications can be distinguished. The first one is based on the “geographical” principle, i.e.: the UK-US system, the Continental system, the Latin American system. In the second classification, systems are clustered based on their typical properties and hierarchy. The upper level defines the objectives that the accounting system focuses on. Next, systems are rated based on whether the state insists on applying the theoretical approach or the actual legislative requirements and business needs. It might be difficult to classify a system as belonging to a specific group if the country’s accounting system is unstable. Thus, in the 60s of the 20th century, New Zealand started to separate from the UK, although many provisions of its accounting system were taken directly from the standards developed by the English Institute of Financial Accountants. In view of the existing challenges and various approaches to the classification of national accounting systems, the importance of such classification can hardly be overestimated. The proximity of national accounting systems in countries that belong to the same model suggests the possibility of harmonization of accounting principles at the international level. Based on the above: - the possibility of grouping national accounting systems into clusters makes it possible to level out the differences between them during standardization; - the convergence of economies of different countries due to the globalization of the world economy contributes to the unification of accounting principles at the global level.